A semiotic analysis of the meaning of “Hikaru” in the song Hikaru Nara by Goose House - Jeminika Isyamy Esika; Akhmad Saifudin (Universitas Dian Nuswantoro, 2025)
This study examines the construction of poetic meaning in the lyrics of the song Hikaru Nara by Goose House using Michael Riffaterre’s semiotic framework, supported by conceptual metaphor theory. The research aims to uncover the mechanisms of indirect expression, as well as to identify the matrix, model, variants, and hypogram that structure the symbolic meaning of the lyrics. A qualitative descriptive method with content analysis was employed, focusing on textual units containing metaphors, symbols, and semantic deviations. The findings reveal that the meaning of the lyrics is constructed through symbolic transformations rooted in natural imagery and journey metaphors. The matrix of the song reflects an inner transformation from suffering and darkness toward hope and emotional renewal, triggered by the presence of a significant figure represented as “light.” The model is dominated by natural and journey metaphors, while the variants appear in recurring symbols such as light, rain, stars, and sky. The hermeneutic reading demonstrates that meaning emerges dynamically through the interaction between linguistic signs, listener experiences, and socio-cultural contexts. This study contributes to the development of literary semiotics by demonstrating the relevance of Riffaterre’s theory in analyzing contemporary Japanese song lyrics and highlighting the role of conceptual metaphor in shaping poetic meaning.